Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Five years nitrogen reduction management shifted soil bacterial community structure and function in high-yielding ‘super’ rice cultivation - Juanjuan Wang; Ruqing Xie; Nanan He; Wanlu Wang; Guiliang Wang; Yanju Yang; Qing Hu; Haitao Zhao; Xiaoqing Qian (Agriculture, Ecosystems & Environment, 2024)

Operational Modal Analysis of Offshore Wind Turbine Tower under Ambient Excitation - Peng Zhang; Zhengjie He; Chunyi Cui; Liang Ren; Ruqing Yao (Journal of Marine Science and Engineering, 2022)
The condition of an offshore wind turbine (OWT) should be monitored to assure its reliability against various environmental loads and affections. The modal parameters of the OWT can be used as an indicator of its condition. This paper combines the Kalman filter, the random decrement technique (RDT), and the stochastic subspace identification (SSI) methods and proposes an RDT-SSI method to estimate the operational frequency of an OWT subjected to ambient excitation. This method imposes no requirement on the input/loads; therefore, it is relatively easy for field application. An experimental study with a small-scale OWT was conducted to verify the accuracy of the proposed RDT-SSI method. The test results implied that the frequency estimated by the RDT-SSI method is close to that estimated by an impact hammer test. Moreover, the small-scale OWT was buried at different embedment depths to simulate the influence of the scouring phenomenon, and the frequency of the OWT decreased with decreasing embedment depth. Additionally, the bolts at the root of the turbine blades were also loosened to investigate their influence on the frequency. As more blades were loosened, the identified frequency of the OWT also decreased, indicating that the proposed RDT-SSI method can be employed for the health monitoring of an OWT.